2010
DOI: 10.1080/00087114.2010.10589733
|View full text |Cite
|
Sign up to set email alerts
|

Cytosystematics of threeOnobrychisspecies (Fabaceae) in Iran

Abstract: In this study, we describe the morphological characters and meiotic chromosome number and behavior of different wild populations belonging to Onobrychis viciifolia Scop., O. transcaucasica Grossh. and O. altissima Grossh. belonging to Onobrychis sect. Onobrychis in Iran. All Iranian populations of O. viciifolia and O. altissima studied here were tetraploid and showed 2n = 4x = 28 chromosome number, but O. transcaucasica populations were diploid. The basic chromosome number (x = 7) is consistent with the propos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Onobrychis viciifolia, a summary of the classification (Širjaev, 1925) Genus =OnobrychisHymenobrychis taxonomy of different species within the Onobrychis genus and to determine its evolution. Through the karyotype analysis of different Onobrychis species, it has been suggested that the two populations of Onobrychis transcaucasica should be placed in one group, while Onobrychis altissima and O. viciifolia should be placed in a second group (Massoud et al, 2010). During one of the last karyotype analyses developed in sainfoin, the 2C value was determined to be approximately 2.5 pg (Hayot Carbonero et al, 2013).…”
Section: Polyploidy and Karyotype Of Onobrychis Viciifoliamentioning
confidence: 99%
“…Onobrychis viciifolia, a summary of the classification (Širjaev, 1925) Genus =OnobrychisHymenobrychis taxonomy of different species within the Onobrychis genus and to determine its evolution. Through the karyotype analysis of different Onobrychis species, it has been suggested that the two populations of Onobrychis transcaucasica should be placed in one group, while Onobrychis altissima and O. viciifolia should be placed in a second group (Massoud et al, 2010). During one of the last karyotype analyses developed in sainfoin, the 2C value was determined to be approximately 2.5 pg (Hayot Carbonero et al, 2013).…”
Section: Polyploidy and Karyotype Of Onobrychis Viciifoliamentioning
confidence: 99%